2005
DOI: 10.1007/s00208-004-0625-z
|View full text |Cite
|
Sign up to set email alerts
|

On smoothness of L3,?-solutions to the Navier?Stokes equations up to boundary

Abstract: We show that L 3,∞ -solutions to the three-dimensional NavierStokes equations near a flat part of the boundary are smooth.1991 Mathematical subject classification (Amer. Math. Soc.): 35K, 76D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 12 publications
3
43
0
1
Order By: Relevance
“…The endpoint case (p, q) = (3, ∞) was recently resolved [7] (also see the references in [34,7] for earlier results in subclasses). Similar regularity criteria have been established near the boundary [36,12,28].…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…The endpoint case (p, q) = (3, ∞) was recently resolved [7] (also see the references in [34,7] for earlier results in subclasses). Similar regularity criteria have been established near the boundary [36,12,28].…”
Section: Introductionsupporting
confidence: 56%
“…The second term in (28) is just N r|(∇h) r |. For the first term in (28), use the Poincaré-Sobolev inequality, the mean-value property, and an interior estimate:…”
Section: Proof Of Theorem 11 (Ii)mentioning
confidence: 99%
“…However, there is an interesting marginal case s = 3, in which no estimate of type (1.5) is known. In papers [3,14,17], it has been shown that lim sup t↑T v(·, t) L 3 ( ) = ∞ (1.6) for = R 3 , = R 3 + := {x = (x i ) ∈ R 3 : x 3 > 0} and for being a bounded domain with sufficiently smooth boundary.…”
Section: 4)mentioning
confidence: 99%
“…In particular, this required the unique solvability theorem for the inverse heat conduction equation with lower terms in the half-space (see [18]- [22]). …”
Section: §1 Introductionmentioning
confidence: 99%